Avoided global warming emissions with the adoption of biofuel policies in Spain. (15th July 2009) - Lechon, Y.; Cabal, H.; Caldes, N.; Santamaria, M., R. Saez
The objective of this study is to assess the Greenhouse Gas (GHG) emissions in the production and use of biofuels in Spain considering different crop production alternatives, including the possible import of raw materials. Avoided GHG emissions due to the substitution of conventional transport fuels with biofuels are then quantified. The studied biofuels are bioethanol from cereal crops and biodiesel from crude vegetable oil and waste vegetable oil. Several blends of these biofuels with gasoline and diesel are also studied. A Life Cycle Assessment (LCA) of these fuels is carried out. The stakeholders were involved early in the process, setting the scope of the analysis and providing the relevant data. The results shown are GHG emissions in the production and distribution of these fuels. The benefits, in terms of GHG savings, of the adoption of the biofuel introduction objectives at the national and European levels are also quantified.